Disentangling the role of Limosilactobacillus reuteri D-lactate in lipid metabolism - Romero, Brian Nathan Saavedra (2022)
Tese de mestrado, Ciências Biofarmacêuticas, 2022, Universidade de Lisboa, Faculdade de Farmácia.